2013
DOI: 10.2174/1874192401307010061
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence of Early Vascular Disease in Patients with Obstructive Sleep Apnoea Without Known Comorbidities? Preliminary Findings

Abstract: We evaluated early atherosclerotic lesions in 20 non-smokers with newly diagnosed Obstructive Sleep Apnoea (OSA) and without known comorbidities by measuring common carotid artery intima media thickness (CCA-IMT), transcranial Doppler ultrasound (TCD), and ankle brachial index (ABI). These were compared with 20 healthy age- and BMI-matched controls. In OSA patients, CCA-IMT was not significantly higher vs. controls (0.74±0.17 vs. 0.66±0.12 mm, p=0.201) and it was positively correlated with neck circumference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
5
0
1
Order By: Relevance
“…It has been shown that elevated concentration of free fatty acid increased oxidative stress [[ 33 ]] and provoked vascular endothelial injury [[ 34 ]]. In addition, NC is an important predictor for obstructive sleep apnea (OSA), and OSA has been associated with arterial stiffening [[ 35 ],[ 36 ]].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated concentration of free fatty acid increased oxidative stress [[ 33 ]] and provoked vascular endothelial injury [[ 34 ]]. In addition, NC is an important predictor for obstructive sleep apnea (OSA), and OSA has been associated with arterial stiffening [[ 35 ],[ 36 ]].…”
Section: Discussionmentioning
confidence: 99%
“…In the OSA setting, oxidative stress combined with low-grade inflammation and sympathetic over-activity have been reported to play a key role in promoting endothelial damage and atherosclerosis, by increasing lipid peroxidation and reactive oxygen species and impairing serum antioxidant capacity. In the last two decades, numerous research groups have investigated the relationship between OSA and CIMT with not univocal results [49][50][51][52].…”
Section: Carotid Atherosclerosismentioning
confidence: 99%
“…En cuanto al tabaquismo, el ser fumador aumenta 6 veces el riesgo en hombres y dos veces en mujeres si el consumo en promedio es de 20 cigarrillos día, adicional se ha visto como el dejar de fumar disminuye signifi cativamente el riesgo de padecer ECV (Tabla 1). Otras condiciones en el paciente diabético afectan de igual manera la evaluación, el padecer por más de 10 años DM, una tasa de fi ltración glomerular disminuida, proteinuria y microalbuminuria; en este punto no hay datos sobre reclasifi cación, discriminación, calibración o costo efecto que permitan adicionar estos últimos tres factores a los modelos actuales aunque su presencia junto a la DM incrementan el riesgo; hipertensión arterial, hiperlipidemia, padecer esteatosis hepática no alcohólica, disfunción eréctil, apnea obstructiva del sueño, hiperglucemia cróni-ca e hipoglicemia severa (20,(22)(23)(24)(25)(26).…”
Section: Evaluación De Riesgo Cardiovascular En Pacientes Con Diabetesunclassified